2021
DOI: 10.1111/jre.12958
|View full text |Cite
|
Sign up to set email alerts
|

The Th17/Treg cell balance: crosstalk among the immune system, bone and microbes in periodontitis

Abstract: Periodontopathic bacteria constantly stimulate the host, which causes an immune response, leading to host‐induced periodontal tissue damage. The complex interaction and imbalance between Th17 and Treg cells may be critical in the pathogenesis of periodontitis. Furthermore, the RANKL/RANK/OPG system plays a significant role in periodontitis bone metabolism, and its relationship with the Th17/Treg cell imbalance may be a bridge between periodontal bone metabolism and the immune system. This article reviews the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 132 publications
2
21
0
Order By: Relevance
“…Cytokines produced by Th1 and Th17 cells also induce the production of chemokines to recruit neutrophils and macrophages to enhance the innate immune response ( 120 , 134 ). Th2 and Treg lymphocytes produce cytokines such as IL-4, IL-10, IL-27, IL-35, and TGF-β that resolve inflammation or reduce bone resorption ( 135 137 ). Th2/Treg-secreted cytokines also upregulate OPG to inhibit bone resorption ( 132 , 133 ).…”
Section: Periodontal Diseasementioning
confidence: 99%
“…Cytokines produced by Th1 and Th17 cells also induce the production of chemokines to recruit neutrophils and macrophages to enhance the innate immune response ( 120 , 134 ). Th2 and Treg lymphocytes produce cytokines such as IL-4, IL-10, IL-27, IL-35, and TGF-β that resolve inflammation or reduce bone resorption ( 135 137 ). Th2/Treg-secreted cytokines also upregulate OPG to inhibit bone resorption ( 132 , 133 ).…”
Section: Periodontal Diseasementioning
confidence: 99%
“…Impaired bone repair and reconstruction in in amed periodontium remains a major clinical challenge for bone regeneration in periodontitis patients 31 . The imbalance between Th17 and Treg cells in periodontal tissue is closely related to the progression of in ammation 10 . An elevated Th17/Treg ratio in peripheral blood is also associated with periodontal in ammation and alveolar bone destruction 11,32 .…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, we found that IL-17 promoted bone resorption via osteocyte-speci c signaling pathways, and also regulated the osteogenesis of mesenchymal stem cells (MSCs) 7,8,9 . Conversely, Treg cells participate in immunosuppression and tissue repair to maintain periodontal health, depending on sustained high expression of FOXP3 and interleukin-10 (IL-10) 10 . Rather than in periodontal tissue, an elevated Th17/Treg ratio in peripheral blood without systemic diseases is also associated with periodontal in ammation and alveolar bone destruction 2,11 .…”
Section: Introductionmentioning
confidence: 99%
“…By contrast, Treg is considered to play a protective role in periodontal tissue and can inhibit the differentiation of Th1, Th2, and Th17. Generally, Treg is regarded as an important cell in maintaining periodontal immune homeostasis 164–166 . The production of TGF‐β and T lymphocyte‐associated molecule 4 (cytotoxic T cell antigen 4) by Treg cells could diminish inflammatory responses, thus reduce the severity of periodontitis 167 …”
Section: Effects Of Immune Cells and Immune Senescence In Periodontitismentioning
confidence: 99%
“…Generally, Treg is regarded as an important cell in maintaining periodontal immune homeostasis. [164][165][166] The production of TGF-β and T lymphocyte-associated molecule 4 (cytotoxic T cell antigen 4) by Treg cells could diminish inflammatory responses, thus reduce the severity of periodontitis. 167…”
Section: Immune Functions Of T Cells In Periodontitismentioning
confidence: 99%